Infrared signature of structural isomers of gas– phase M+(N2O)n(M = Cu, Ag, Au) ion–molecule complexes - Cunningham, E; Gentleman, A; Beardsmore, P; Iskra, A; Mackenzie, S (American Chemical Society, 2017)
Gas-phase metal ion–ligand complexes offer model environments to study molecular interactions which are key to many catalytic processes. Here, we present a combined experimental and computational study of M+(N2O)n [M= Cu, Ag, Au; n = 2–7] complexes. The spectra provide clear evidence for both nitrogen– and oxygen– bound ligands giving rise to a wide range of structural isomers for each complex studied. The evolution of the complex structures observed as well as spectral trends for each metal center are interpreted in terms of a molecular orbital binding picture and resulting calculated ligand binding energies. Given the environmental importance of nitrogen oxides, these results have implications for metal–catalysed removal of nitrous oxide and, particularly, the prospect of initiating infrared–driven isomer–selective chemistry in size–selected complexes.